Resocialization for Victims of Sexual Violence at the Social Rehabilitation Center for Children who Need Special Protection (BRSAMPK) Rumbai Pekanbaru - Rio Alfasyah; Rd. Siti Sofro Sidiq; Risdayati Risdayati (Jurnal Mantik, 2021)
Implementation of resocialization for victims of sexual violence at the social rehabilitation center for children who need special protection (BRSAMPK) Rumbai Pekanbaru. This research was conducted at BRSAMPK Rumbai Pekanbaru. The purpose of this research is to find out the resocialization process carried out by social workers to children who are victims of sexual violence and to find out the obstacles that affect the implementation of the resocialization process carried out by social workers to children who are victims of sexual violence. This study uses a descriptive qualitative approach using purposive sampling technique. The number of informants in this study were five informants and one key informant. The results obtained are that social workers carry out the stages of resocialization of child victims of sexual violence with interventions carried out through psychosocial therapy. Resocialization in the social environment of children who are victims of sexual violence is also carried out, including the family environment, community, schools, course institutions where social workers advocate so that children can be well received in that environment. Social workers carry out a monitoring process that is carried out at the advanced guidance stage to see the developments that occur in children after social rehabilitation is carried out. Meanwhile, the obstacles encountered by social workers do not come from internal social workers. However, the obstacle comes from the child himself being traumatized by the events he has experienced. Other obstacles arise in the family environment that rejects the existence of children and the community environment that carries out a bad stigma against children.